Self-reflection in cognitive behavioural therapy and supervision - Prasko, Jan; Mozny, Petr; Novotny, Miroslav; Slepecky, Milos; Vyskocilova, Jana (Biomedical papers, 2012)
Objective: Supervision is a basic part of training and ongoing education in cognitive behavioural therapy. Self-reflection is an important part of supervision. The conscious understanding of one's own emotions, feelings, thoughts, and attitudes at the time of their occurrence, and the ability to continuously follow and recognize them are among the most important abilities of both therapists and supervisors. The objective of this article is to review aspects related to supervision in cognitive behavioural therapy and self-reflection in the literature.Methods: This is a narrative review. A literature review was performed using the PubMed, SciVerse Scopus, and Web of Science databases; additional references were found through bibliography reviews of relevant articles published prior to July 2011. The databases were searched for articles containing the following keywords: cognitive behavioural therapy, self-reflection, therapeutic relationship, training, supervision, transference, and countertransference. The review also includes information from monographs referred to by other reviews.Results: We discuss conceptual aspects related to supervision and the role of self-reflection. Self-reflection in therapy is a continuous process which is essential for the establishment of a therapeutic relationship, the professional growth of the therapist, and the ongoing development of therapeutic skills. Recognizing one's own emotions is a basic skill from which other skills necessary for both therapy and emotional self-control stem. Therapists who are skilled in understanding their inner emotions during their encounters with clients are better at making decisions, distinguishing their needs from their clients' needs, understanding transference and countertransference, and considering an optimal response at any time during a session. They know how to handle their feelings so that these correspond with the situation and their response is in the client's best interest. The ability to self-reflect increases the ability to perceive other people's inner emotions, kindles altruism, and increases attunement to subtle signals indicating what others need or want. Self-reflection may be practised by the therapists themselves using traditional cognitive behavioural therapy techniques, or it may be learned in the course of supervision. If therapists are unable to recognize their own thoughts and feelings, or the effects of their attitudes in a therapeutic situation, then they are helpless against these thoughts and feelings, which may control the therapist's behaviour to the disadvantage of the client and therapist alike.Conclusion: Training and supervision focused on self-reflection are beneficial to both supervisees and their clients. The more experienced the supervisor is, the more self-reflection used in therapy and supervision.
Keywords: supervision; cognitive behavioural therapy; self-reflection; transference; countertransference